Code gray : death, life, and uncertainty in the ER - Nahvi, Farzon A. (Simon & Schuster, 2023)
A medical memoir focusing on one emergency room doctor's shift in an urban ER follows the experiences of real patients and focuses on the story of a forty-three-year-old woman who arrives in sudden cardiac arrest and the challenges it presents for physicians.